Decision Support System for Determining the Best Nurse at Grandmed Hospital Using the Simple Additive Weighting Method - Nuraisana (Jurnal ICT : Information and Communication Technologies, 2022)
A decision support system is a combination of individual intelligence sources with component capabilities to improve decision quality. Decision support system is also a computer-based information system for decision-making management that handles semi-structured problems. The purpose of this study was to create an application for nurse employees at Grandmed Hospital. Based on the results of the research that has been discussed, the Decision Support System for Determining the Best Nurse at Grandmed Hospital using the Simple Additive Wieghting (SAW) method with the benefit of being able to make it easier to process nurse data and make it easier to determine the best nurse for a nurse promotion at Grandmed Hospital.